Social Software and the Social Sciences - Dowding, Keith; Verbrugge, Rineke (Discourses on Social Software, 2009)
Our Philosopher, Political Scientist, Logician and Ethicist meet yet again at a conference after lunch, and are joined by some new discussants: a Computer Programmer and a Cognitive Scientist, and the discussion is moderated by a Chair.